DOI: 10.22215/etd/2007-06607
|View full text |Cite
|
Sign up to set email alerts
|

Performance-based seismic design of building structures

Abstract: Direction du Patrimoine de I'edition 395, rue W ellington Ottawa ON K1A 0N4 CanadaBien que ces formulaires aient inclus dans la pagination, il n'y aura aucun contenu manquant. i * i Canada Reproduced with permission of the copyright owner. Further reproduction prohibited without permission. AbstractA new method for the displacement-based design (DBD) of a variety of structures to resist the earthquake forces experienced by them is developed. The proposed method requires the determination of yield and ultimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…To ensure the expected ductility demands and energy dissipation capacity, some appropriate detailing measures should be taken. When hit by the strong earthquakes, however, the structures designed by the above methods will suffer inelastic deformations, which is very difficult to predict and control [1][2][3][4][5][6][7][8][9]. The inelastic behavior may include severe yielding and buckling of structural members and connections.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure the expected ductility demands and energy dissipation capacity, some appropriate detailing measures should be taken. When hit by the strong earthquakes, however, the structures designed by the above methods will suffer inelastic deformations, which is very difficult to predict and control [1][2][3][4][5][6][7][8][9]. The inelastic behavior may include severe yielding and buckling of structural members and connections.…”
Section: Introductionmentioning
confidence: 99%
“…These procedures employ a variant of the capacity spectrum method in which the demand is represented by an inelastic response spectrum plotted in the acceleration displacement format for a ductility that is determined from estimates of the yield displacement and acceptable ultimate displacement. Details of the procedures have been presented by Ghorbanie-Asl (2007), Ghorbanie-Asl (2005, 2006) and Humar et al ( , 2010). Humar and Ghorbanie-Asl (2005) introduced a practical displacement-based design procedure in which the maximum acceptable displacement demand on building structures was limited to the least of displacement capacity of the critical component, displacement dictated by performance criteria, and displacement limit to prevent P-A instability.…”
Section: Previous Studies At Carleton Universitymentioning
confidence: 99%
“…Through examples of the design of several reinforced concrete, and steel momentresisting frames as well as braced frames Ghorbanie-Asl (2007) showed that within a few iterations one could estimate the yield and ultimate displacement capacities of the system accurately.…”
Section: Previous Studies At Carleton Universitymentioning
confidence: 99%